Post-weaning Environmental Enrichment in Male CD-1 Mice: Impact on Social Behaviors, Corticosterone Levels and Prefrontal Cytokine Expression in Adulthood - McQuaid, Robyn Jane; Dunn, Roderick; Jacobson-Pick, Shlomit; Anisman, Hymie; Audet, Marie-Claude (Frontiers in Behavioral Neuroscience, 2018)
Environmental enrichment is typically associated with enhanced well-being, improved cognitive function, and stress resilience. However, in some instances grouping adult male mice in enriched conditions promoted a stressful environment, which resulted in elevated endocrine, monoamine, and inflammatory outcomes in response to subsequent stressor exposure. The current investigation examined whether raising male mice in an enriched environment would modulate social and anxiety-like behaviors in early adulthood and influence brain expression of pro-inflammatory cytokines and brain-derived neurotrophic factor (BDNF). Immediately after weaning (postnatal day [PD] 21), CD-1 male mice were housed with their siblings (3/cage) for 6 weeks in an enriched (EE) or a standard (SE) environment. Body weights and aggressive interactions were monitored weekly. Social avoidance behaviors in the social interaction test and anxiety-like behaviors in the elevated-plus maze were examined in early adulthood. Ninety minutes following the behavioral tests, mice were sacrificed and a blood sample and the prefrontal cortex were collected for the determination of plasma corticosterone levels as well as cytokine and BDNF mRNA expression. Mice raised in an EE exhibited more wounds and gained less weight than mice housed in a SE. Enriched mice also spent a greater amount of time in proximity of a social target in the social interaction test and made fewer transitions into the closed arms of the elevated-plus maze. Interestingly, the elevated plasma corticosterone and upregulated prefrontal interleukin (IL)-1 expression observed after the social interaction test among the SE mice were not apparent among those housed in an EE. Enrichment also increased prefrontal BDNF expression, especially among mice that experienced the social interaction test. These results suggest that although raising male mice in an EE may elicit aggressive interactions between sibling cage-mates (as indicated by a high number of wounds), this environment also enhances social behaviors and limits the corticosterone and cytokine impacts of mild social stressors encountered in early adulthood.